Influence of Some Nitrogenous Compounds on Microbial Production of Lactic Acid by Lactobacillous delbrueckii† - Singh, S.P.; Sandani, G.; Dubey, J.K.; Kumar Udai Kumar, A.; Singh, M.K. (Asian Journal of Chemistry, 2010)
The influence of ammonium sulphate, urea, potassium nitrate and ammonium nitrate on the production of lactic acid by Lactobacillus delbrueckii 9649* has been studied. It has been found that urea, ammonium sulphate and ammonium nitrate stimulate the fermentative production of lactic acid whereas potassium nitrate retards the fermentation process.